THE MODEL FOR DEVELOPING LEARNING MANAGEMENT COMPETENCY OF TEACHERS IN SERVICE AREA ENROLLING IN GRADUATE DIPLOMA PROGRAM IN TEACHING PROFESSION - Soparat, Sasithorn; Jamrussri, Pichamon (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2023)
The objectives of this research were to: 1. develop a model for developing the learning management competencies of student teachers in graduate diploma programs in the teaching profession. 2. evaluate the effectiveness of the model for developing learning management competencies. The population for the study included 90 student teachers enrolling in the second semester of the 2022 academic year. The samples were selected by cluster sampling, which included 28 student teachers. The research design is research and development (R and D) using a one-group pre-posttest design. The instruments for the study consisted of 1. The quality evaluation form of the model for developing learning management competency, 2. the test measuring student teachers’s conceptions of learning management, and 3. the evaluation form of learning management competency. The data were analyzed by statistics as arithmetic means, standard deviations, and percentages. The findings of the study revealed the following : 1. The model for developing the learning management competencies of student teachers in graduate diploma programs in the teaching profession consisted of three components: 1) principles used in the model, 2) processes of development, and 3) evaluation. The model was evaluated by five experts and showed that suitability has a high level of accuracy ( = 3.9), possibility ( = 3.8), usefulness ( = 4.15), and suitability ( = 3.45). 2. The results of the effectiveness of the model for developing learning management competency found that 1) the student teachers’ conception of learning management showed the percentage difference in the scores after participating in the model was higher than before with a statistical significance at the .05 level, and 2) the student teachers’ learning management competency in the aspect of designing lesson plans and teaching showed in the above the threshold of 70 percent.